Evaluation of quality of life of visually impaired. - Brasil de Almeida Rebouças, Cristiana; Mendonça de Araújo, Moziane; Cavalcante Braga, Fernanda; Taveira Fernandes, Giselle; Cavalcante Costa, Samira (Revista Brasileira de Enfermagem)
Objective: to evaluate the quality of life of visually impaired using WHOQOL-100. Method: exploratory, descriptive, and quantitative study, performed between April and May 2013 with 20 visually impaired of the Blind Association of Ceará, through interviews. Results: the analysis showed that males predominated (80%), 41-55 years (40%), students (50%) and personal income than the minimum wage (70%). Participants were self-rated with good quality of life (68.75%). The facets with the highest rates were personal relationships (74.06%), sexual activity (66.88%) and spirituality/religion/personal beliefs (65%). With lower rates were financial (43.44%), physical environment: pollution/noise/traffic/climate (46.88%), physical security and protection (37.19%), transport (35.63%) and medication or treatment dependency (8.25%). Conclusion: these results reflect the importance of the nurse to perform health education actions promoting the empowerment, autonomy and guaranteed of access in society for this clientele.